Screening for Acromegaly in Patients with Carpal Tunnel Syndrome: A Prospective Study (ACROCARP) - Zoicas, F.; Kleindienst, A.; Mayr, B.; Buchfelder, M.; Megele, R.; Schöfl, C. (Hormone and Metabolic Research, 2016)
Early diagnosis of acromegaly prevents irreversible comorbidities and facilitates surgical cure. Carpal tunnel syndrome (CTS) is common in acromegaly and patients have often undergone surgery for CTS prior to the diagnosis of acromegaly. We hypothesized that screening CTS-patients for acromegaly could facilitate active case-finding. We prospectively enrolled 196 patients [135 women, 56.9 (range 23–103) years] who presented with CTS for surgery. Patients were asked about 6 symptoms suggestive of acromegaly using a questionnaire calculating a symptom score (0–6 points), and insulin-like-growth factor 1 (IGF-1) was measured. If IGF-1 was increased, IGF-1 measurement was repeated, and random growth hormone (GH) and/or an oral glucose tolerance test (OGTT) with assessment of GH-suppression were performed. The mean symptom score was 1.7±1.3 points. Three patients reported the maximal symptom score of 6 points, but none of them had an increased IGF-1. There was no correlation between the symptom score and IGF-1-SDS (standard deviation score) (r=0.026; p=0.71). Four patients had an IGF-1>2 SDS. In 2 patients acromegaly was ruled out using random GH and OGTT. One patient had normal IGF-1 and random GH at follow-up. One patient refused further diagnostics. In this prospective cohort of patients with CTS, the observed frequency of acromegaly was at most 0.51% (95% CI 0.03 to 2.83%). In this prospective study, none of the 196 patients with CTS had proven acromegaly. Thus, we see no evidence to justify general screening of patients with CTS for acromegaly.
Keywords: acromegaly; carpal tunnel syndrome; screening; IGF-1; growth hormone; pituitary